Calprotectin and TNF trough serum levels identify power Doppler ultrasound synovitis in rheumatoid arthritis and psoriatic arthritis patients in remission or with low disease activity. Issue 1 (December 2016) - Inciarte-Mundo, José; Ramirez, Julio; Hernández, Maria; Ruiz-Esquide, Virginia; Cuervo, Andrea; Cabrera-Villalba, Sonia; Pascal, Mariona; Yagüe, Jordi; Cañete, Juan; Sanmarti, Raimon
Abstract Background Serum levels of calprotectin, a major S100 leucocyte protein, are associated with disease activity in rheumatoid arthritis (RA) and psoriatic arthritis (PsA) patients. Higher drug trough serum levels are associated with good response in patients treated with tumour necrosis factor inhibitors (TNFi). Power Doppler ultrasound (PDUS) synovitis is predictive of flare and progression of structural damage in patients in clinical remission. The purpose of this study was to analyse the accuracy of calprotectin and TNFi trough serum levels in detecting PDUS synovitis in RA and PsA patients in clinical remission or with low disease activity who were receiving TNFi. Methods We conducted a cross-sectional study of 92 patients (42 with RA, 50 with PsA) receiving adalimumab (ADA), etanercept (ETN) or infliximab who were in remission or had low disease activity (28-joint Disease Activity Score based on erythrocyte sedimentation rate <3.2). Associations of calprotectin, TNFi trough serum levels and acute phase reactants with PDUS synovitis were assessed using correlation and linear regression analyses. The accuracy and discriminatory capacity in detecting PDUS synovitis was assessed using ROC curves. Results PDUS synovitis was found in 62.4 % of RA patients and 32 % of PsA patients. Both RA and PsA patients with PDUS synovitis had higher calprotectin levels and lower TNFi trough serum levels. Calprotectin positively correlated with ultrasound scores (allr coefficients >0.50 in RA). Calprotectin correlated with the PDUS synovitis score in patients treated with ADA and ETN. Using PDUS synovitis (yes or no) as the reference variable, calprotectin had an AUC of 0.826. The best cut-off was ≥1.66 μg/ml, with a likelihood ratio of 2.77. C-reactive protein (AUC 0.673) and erythrocyte sedimentation rate (AUC 0.731) had a lower discriminatory capacity. TNFi trough serum levels were significantly associated with PDUS synovitis (OR 0.67, 95 % CI 0.52–0.85, p  < 0.001) but their accuracy (AUC <0.5) was less than that of calprotectin. TNFi trough serum levels were inversely correlated with calprotectin and PDUS synovitis in RA and PsA patients receiving ADA and ETN. Conclusions Calprotectin and TNFi trough serum levels may help identify PDUS synovitis in RA and PsA patients in clinical remission or with low disease activity.